2019
DOI: 10.1007/s00125-019-4863-8
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes defined by severe insulin deficiency occurs after 30 years of age and is commonly treated as type 2 diabetes

Abstract: Aims/hypothesis Late-onset type 1 diabetes can be difficult to identify. Measurement of endogenous insulin secretion using C-peptide provides a gold standard classification of diabetes type in longstanding diabetes that closely relates to treatment requirements. We aimed to determine the prevalence and characteristics of type 1 diabetes defined by severe endogenous insulin deficiency after age 30 and assess whether these individuals are identified and managed as having type 1 diabetes in clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 11 publications
2
114
2
2
Order By: Relevance
“…9 Another study from the UK suggests that type 1 diabetes presenting in later life is often unrecognised or misdiagnosed as type 2 diabetes, despite the need to start insulin therapy soon after diagnosis. 45 According to a study from Italy, there are peaks in the incidence of type 1 diabetes in different age groups, with the highest observed in children and adolescents under 15 years, then a significant decrease in age groups 15-29 years, followed by continuously increasing incidence from the age of 29-49 years. 13 In that study, there were no data for older age groups, but our findings demonstrate a similar pattern across all the available comparable age groups.…”
Section: Discussionmentioning
confidence: 99%
“…9 Another study from the UK suggests that type 1 diabetes presenting in later life is often unrecognised or misdiagnosed as type 2 diabetes, despite the need to start insulin therapy soon after diagnosis. 45 According to a study from Italy, there are peaks in the incidence of type 1 diabetes in different age groups, with the highest observed in children and adolescents under 15 years, then a significant decrease in age groups 15-29 years, followed by continuously increasing incidence from the age of 29-49 years. 13 In that study, there were no data for older age groups, but our findings demonstrate a similar pattern across all the available comparable age groups.…”
Section: Discussionmentioning
confidence: 99%
“…A study using a polygenic risk score based definition of type 1 diabetes revealed that 42 % of all new type 1 manifestations occur after the age of 30 [8]. In contrast, only 38 % of individuals with newly diagnosed type 1 diabetes receive insulin therapy immediately [9]. This underlines that a detection of insulin deficiency present in late onset autoimmune diabetes is particularly important, since the failure of a timely initiation of insulin therapy and/ or an inadequate therapy with ketoacido-Published online: 2020-09-18 sis-promoting agents such as SGLT2 inhibitors could have fatal consequences for type 1 diabetes patients [10].…”
Section: Importance Of Insulin Secretionmentioning
confidence: 99%
“…Following on from their monogenic diabetes calculator, researchers at Exeter, Oxford and Dundee Universities have developed a new calculator to help clinicians classify whether someone has type 1 diabetes or type 2 diabetes . The need for such a calculator is evident as a study earlier this year from Exeter suggested that nearly 40% of adults who developed type 1 diabetes were initially misdiagnosed and treated for type 2 diabetes .…”
Section: Right Diagnosis?mentioning
confidence: 99%